Artificial intelligence in educational mathematics: opportunities and threats - Манчинська, Н. Б. (KNPU, 2023)
The integration of artificial intelligence (AI) in mathematics education offers new learning opportunities but also presents challenges such as academic integrity violations, misinformation, and student over-reliance on technology. Misuse of AI can result in a lack of genuine understanding. Educators must guide students to use AI responsibly, verifying its outputs and avoiding cheating. Emphasizing logical thinking, analysis, and creativity, teachers should employ diverse assessment methods to accurately evaluate student knowledge and skills, ensuring AI enhances rather than replaces learning.
Keywords: Mathematics education; artificial intelligence; academic integrity; responsible AI use; educational technology; assessment methods